Fluorocoxib A loaded nanoparticles enable targeted visualization of cyclooxygenase-2 in inflammation and cancer. (June 2016) - Uddin, Md. Jashim; Werfel, Thomas A.; Crews, Brenda C.; Gupta, Mukesh K.; Kavanaugh, Taylor E.; Kingsley, Philip J.; Boyd, Kelli; Marnett, Lawrence J.; Duvall, Craig L.
Abstract: Cyclooxygenase-2 (COX-2) is expressed in virtually all solid tumors and its overexpression is a hallmark of inflammation. Thus, it is a potentially powerful biomarker for the early clinical detection of inflammatory disease and human cancers. We report a reactive oxygen species (ROS) responsive micellar nanoparticle, PPS-b-POEGA, that solubilizes the first fluorescent COX-2-selective inhibitor fluorocoxib A (FA) for COX-2 visualization in vivo. Pharmacokinetics and biodistribution of FA-PPS-b-POEGA nanoparticles (FA-NPs) were assessed after a fully-aqueous intravenous (i.v.) administration in wild-type mice and revealed 4–8 h post-injection as an optimal fluorescent imaging window. Carrageenan-induced inflammation in the rat and mouse footpads and 1483 HNSCC tumor xenografts were successfully visualized by FA-NPs with fluorescence up to 10-fold higher than that of normal tissues. The targeted binding of the FA cargo was blocked by pretreatment with the COX-2 inhibitor indomethacin, confirming COX-2-specific binding and local retention of FA at pathological sites. Our collective data indicate that FA-NPs are the first i.v.-ready FA formulation, provide high signal-to-noise in inflamed, premalignant, and malignant tissues, and will uniquely enable clinical translation of the poorly water-soluble FA compound. Graphical abstract: